(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Physical setting and socio-economic characteristics have an impact on growth of an area in general and similarly population growth in an area is also the outcome of fertility, mortality and migration in particular. The urban growth rate in Himachal Pradesh is moderate. The present paper attempts to study the growth of urban population in Himachal Pradesh. The hill state of Himachal Pradesh urban centers evolved at different periods, at different location and with different objectives. Besides, these urban centers have diverse physical characteristics and their different economic base. The basic premise is that there are differentials in population growth of town in term of size and other characteristics of towns. It is analysed that higher order administrative centers, such as district headquarters are growing relatively fast due to considerable immigration. By contrast, growth rate of cantonment towns has been slow because of their exceptionally low rate of natural increase.